523 STAGING PET-CT LENGTH AND SURVIVAL IN PATIENTS UNDERGOING RESECTIONS FOR ESOPHAGEAL ADENOCARCINOMA. (17th September 2021) - Coe, Peter; Lo, Terence; Peckham-Cooper, Adam; Sarela, Abeezar; Hayden, Jeremy; Mehta, Samir
Abstract: : Esophagectomy is associated with considerable morbidity and mortality and a significant reduction in quality of life. Early identification of patients at high-risk of early recurrence and death would allow a more informed discussion about the benefits of surgery. Previous studies have shown that histological tumour length may be an independent predictor of survival. In this study we have determined whether tumour length at diagnosis can predict survival after esophagectomy. Methods: From a single-centre prospective clinical database (2012 to 2018), we obtained data on tumour characteristics and 18F-FDG PET-CT (PET-CT) measurement of tumour length. The primary endpoint was overall survival (OS).We performed multivariate modelling using semi-parametric Cox models, and additionally explored flexible parametric modelling using fractional polynomials to explore non-linear relationships. Relationships between tumour length and known prognosticators were assessed using standard statistical techniques. Results: We included 300 patients with esophageal adenocarcinoma and pre-operative PET-CT imaging. Tumour length was measurable on PET-CT in 91% of patients (274) (median 4.7 cm, range 1.3–12). 77% of patients received neo-adjuvant therapy. One and five-year overall survival rates were 79% and 44%, respectively. There was no relationship between survival and tumour length. One year survival for patients with tumours greater than 8 cm was 67% compared with 82% for tumours less than 8 cm although this was not statistically significant (p = 0.86). Tumour length was associated with tumour stage but not resection margin positivity or number of positive lymph nodes. Conclusion: Tumour length as measured by PET-CT at diagnosis does not predict survival in patients undergoing esophagectomy for esophageal adenocarcinoma. This data supports the notion that tumour length by itself should not be used as a means of stratifying treatment.